Reflections on the Use of Evidence in Child Welfare: A Commentary on Barth et al. (July 2022) - Font, Sarah A.
To create a child welfare system that meets the needs of abused and neglected children, it is essential to critically evaluate core claims and assumptions about how the current child welfare system operates and its impacts on children and families. Yet, misleading and false claims are frequently repeated in academic, professional, and media outlets. Barth and colleagues (2021) sought to name and evaluate some of these claims, reasserting the central role of research evidence in policy and practice debates. In this commentary, I argue that a commitment to "consider the evidence" may do little to improve the quality of policies or practices in the child welfare system. Rather, I assert that because research findings are commonly mischaracterized and overgeneralized, we are left with widespread disagreement about what to conclude from existing research and how certain those conclusions are.